Optimization of Povidone K-30 and Sodium Starch Glycolate on Levofloxacin Tablet by Factorial Design - Setyawan, Dwi; Soeratri, Widji; Nuruddin, Mahrus Naufal; Paramita, Diajeng Putri; Widjaja, Bambang (Jurnal ILMU DASAR, 2020)
The aim of this study was to determine the effect of binder and disintegrant excipients toward tablet properties of levofloxacin as the latter tends to suffer brittle fracture upon compression. The excipients used were povidone K-30 as the binder and sodium starch glycolate (SSG) as the disintegrant which the tablets were formulated according to factorial design 22 with two factors and two levels on each factor. Four formulas were prepared by wet granulation method using 2 and 4% of each povidone K-30 and sodium starch glycolate in various compositions. Tablet properties were evaluated for its hardness, friability, and disintegration time as well as dissolution profile. The data obtained was statistically analyzed using Minitab® 17 software to optimize the formulation and resulted in different impacts caused by each excipient. Povidone K-30 exhibited an increment in hardness, friability, disintegration time but a decrease indissolution profile of levofloxacin tablet. SSG decreased hardnessand disintegration time, but increased friability and dissolution profile of levofloxacin tablet. Overlaid contour plot showed that the optimal formula regarding tablet properties of friability, disintegration time, and dissolution profile is in composition of 2.01% povidone K-30 and 2.01% sodium starch glycolate. Keywords: levofloxacin tablet, povidone K-30, sodium starch glycolate, factorial design.